Assessment of Natural Radioactivity Levels and Radiation Hazards for Soil Samples Used in Erbil Governorate, Iraqi Kurdistan - Hussein, Zakariya A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
In this work, the activity concentrations of natural radionuclides 226Ra, 232Th and 40K in soil samples from Erbil governorate, Iraqi Kurdistan were investigated by a gamma-spectroscopy system based on high-purity germanium (HPGe) detector. This is to assess the dose of radionuclides exposure to the population, knowing the health risks and to have a baseline for future changes in the environmental radioactivity. It was found that the activity concentrations of 226Ra, 232Th and 40K were ranged from (14.6 ± 1.6 to 38.2 ± 2.8 Bq.kg-1), (4.5 ± 1.4 to 52.4 ± 5.8 Bq.kg-1) and ( 302.8 ± 12.6 to 388.6 ± 12.8 Bq.kg-1), respectively. The measured activity concentrations for these radionuclides were compared with the reported data of other countries and with the worldwide average activity of soil. Radium equivalent activities, absorbed dose rate, excess lifetime cancer risk and the values of hazard indices were calculated for the measured samples to assess the radiation hazard of the natural radioactivity in all samples to the people. It was concluded that the radium equivalent activities of the studied samples are below the internationally accepted values. These results show that annual effective dose absorbed via occupant from activity construction of soil samples used in the under place is below 1.0 mSv.y-1. It is concluded that the assessment radioactivity of soil are within acceptable levels and does not pose any health hazard to the population.